Epistemic Modality in Vietnamese EFL Students’ Argumentative Writing - Trang Thu Nguyen (Yayasan Visi Intan Permata, 2025)
Epistemic modality plays a crucial role in expressing a writer’s opinion, degree of certainty, and engagement with the reader, particularly in argumentative writing. Inspired by prior research, this paper aims to explore the epistemic modality markers used in 50 essays written by English-majored students. A combination of quantitative and qualitative data was employed to discover how the participants have used linguistic devices to express different degrees of commitment and categories of epistemic devices. The results suggest that epistemic modality is a common feature in this genre, with roughly one-third of the sentences in the data containing epistemic elements. The findings also show a clear preference for expressing probability through modal verbs. Additionally, the data reveal frequent use of epistemic lexical verbs and adjectives to convey certainty and modal verbs to denote probability. The study concludes with pedagogical recommendations for enhancing students’ use of epistemic modality in argumentative essays.